The Effectiveness Of The “Lab Rotation” Model Within Hybrid Learning For Developing Language Skills In Graduating Students (Journal of Pedagogical Inventions and Practices, 2025)
This study explores the implementation of the Lab-Rotation model within hybrid education to support effective teaching and learning in schools, particularly for foreign language instruction. The model integrates traditional classroom lessons with computer lab sessions, offering students an interactive and flexible learning environment. It enhances student motivation, improves academic outcomes, and provides targeted support for both underperforming and advanced learners. The research highlights the practical feasibility of applying this model in Uzbek schools, considering existing infrastructure and government initiatives aimed at professional development for teachers. Furthermore, the Lab-Rotation approach facilitates individualized learning pacing, interactive feedback, and continuous knowledge assessment using digital technologies. The model’s applicability extends beyond natural sciences to humanities subjects such as English, contributing to the comprehensive development of language skills. Overall, the Lab-Rotation model demonstrates significant potential to improve student engagement, mastery of subject matter, and preparation for higher education and competitive academic environments.